Investigation of biodegradation behaviour of an Mg‐1Ca alloy influenced by heat treatment and applying plasma‐chemical oxidation layers. Issue 7 (2nd March 2012) - Schmigalla, S.; Bender, S.; Heyn, A.; Schmidt, J.; Hort, N.
Abstract The degradation behaviour of an Mg‐1Ca alloy is investigated in vitro to figure out the possibilities of influencing the degradation behaviour of such an alloy by applying heat treatment as well as the use of a coating system based on plasma‐chemical oxidation. It is shown that an optimised solution annealing (T4‐heat treatment) can reduce the degradation rate while an additional ageing between 240 and 300 °C (T6‐heat treatment) increases it. A coating generated by plasma‐chemical oxidation reduces the degradation rate in the immersion test. Its effect is depending on the former heat treatment of the Mg‐1Ca alloy as well as on the parameter during plasma‐chemical oxidation.